Educational Pathways from Classroom and Beyond: Exploring the Learning Experiences of Nursing Student - Saculingan, Nicole Lorraine; C. Cabalang, Hylene Yancey; T. Cardona, Leal Carisse; N. Espiritu, Czarina; M. Garcia, Sheila Patricia; C. Ramel, Junelyn; Z. Tabuyan, Mae Joyce; E. Abonalla, Arby James; Aggari, Michael I.; Arreglo, Elenita M.; Bernabe, Patrick Benj S.; Marced, Joel John Dela; Flores, Annabelle; Guevarra, Cecile F.; Grageda, Florence B.; Lapitan, Marie Anne; Lopez, Mary Ann; Salcedo, Trinita; Vargas, Ruby (MALATA SAINS INDONESIA, 2024)
Introduction: This study examined how learning experiences influenced the academic performance of second-year nursing students. According to the findings of this study, the perspective frameworks offered by nursing learning experiences not only teach certain types of skills but also provide the information and support needed for wider practice. Objective: The aim of this study was to look at how various educational paths influence second-year nursing students. Furthermore, it explores phenomena pertaining to nursing students in order to determine how these things impact their experiences. Methods: an open-ended interview combined with a qualitative phenomenology research instrument, the researchers in this study used a purposive sample strategy to choose their sample. A total of 15 second-year nursing students from Quezon City's prestigious educational institution participated in the study. Researchers interviewed the second-year nursing students with a qualitative interview format. Result: In line with identification and study, practical experience seemed to be a significant part of these measurements. This study has far-reaching implications for education, including how skills are taught and how to integrate various learning experiences. Those involved in the study called attention to issues about being busy, time management, and the quality of the instruction equipment. Students brought up issues with adhering to a strict timetable and some issues with information overload regarding new technology, including better overhead projectors and instructional materials. Conclusion: This study showed how realizing these elements could assist nursing students by establishing a more rational timetable, providing more resources, and informing them in advance about where their clinical experience will be. It emphasizes the importance of how a positive learning environment is essential to a student's capacity to focus, understand the material right away, and store it in students memory.